Agroecological Production Infrastructure of Agro-Industrial Complex: Problems and Solutions, International - Атамас, Олександр Петрович; Atamas, Oleksandr; Атамас, Петро Йосипович; Atamas, Petro (International Association of Engineering and Management Education (IAEME), 2019)
Today, the issues of organization and functioning of the production infra-structure of agricultural entities in market relations, when the existing system is destroyed and the new one has not yet been created, have not been sufficient-ly studied. The hopes that the problem of increasing the economic integration of producers, suppliers of material and technical resources and services with rural producers would be solved automatically, through market mechanisms, that prices would become cheaper and the quality of services would improve, equivalent exchange and administrative relations would be ensured, failed. The measures of the state to improve the situation were discrete. In this regard, scientific generalizations of the practice of organizing pro-duction infrastructure in agricultural entities, analysis of the level of scrutiny of the problem suggest that the published works mainly dealt with general con-cepts of building infrastructure and services in the agroindustrial sector, devel-oping areas of maintenance supply, agrochemical, transport service, leasing and repair of equipment. However, the formation of a specialized agroecologi-cal service within the production infrastructure that is able to provide high-quality environmental control over agricultural production has been insuffi-ciently studied. Сьогодні проблеми організації та функціонування виробничої інфраструктури сільськогосподарських підприємств у ринкових відносинах, коли існуюча система руйнується, а нова ще не створена, недостатньо вивчені. Сподівання, що проблема підвищення економічної інтеграції виробників, постачальників матеріальних і технічних ресурсів і послуг з сільськими виробниками буде вирішена автоматично, через ринкові механізми, щоб ціни стали дешевшими, а якість послуг покращиться, еквівалентні обміну та адміністративні відносини були б забезпечені, не вдалося. Заходи держави щодо поліпшення ситуації були дискретними. У зв'язку з цим, наукові узагальнення практики організації виробничої інфраструктури в сільськогосподарських підприємствах, аналіз рівня перевірки проблеми свідчать про те, що опубліковані роботи в основному стосувалися загальних концепцій побудови інфраструктури та послуг в агропромисловому секторі, розвиток напрямків технічного обслуговування, агрохімічного, транспортного обслуговування, оренди та ремонту обладнання. Проте недостатньо вивчено формування спеціалізованої агроекологічної служби в межах виробничої інфраструктури, здатної забезпечити якісний екологічний контроль над сільськогосподарським виробництвом.
Агроекологічна виробнича інфраструктура агропромислового комплексу: проблеми та рішення
Keywords: industrial infrastructure; промислова інфраструктура; environmental safety; екологічна безпека; agroecology; агроекологія; economic integration; економічна інтеграція; environmental and economic regulation; екологічне та економічне регулювання